Economic Methods of Land Use In Agriculture - Islamov Farkhod Rakhmatullayevich (Genius Journals, 2024)
This article discusses the problems of protecting agricultural lands in the Republic of Uzbekistan. During the study, issues of improving the existing unified land tax system were considered and, on their basis, proposals and recommendations were made.
Keywords: land; rational use of land; agricultural land